Valuing Changes in Political Networks: Evidence from Campaign Contributions to Close Congressional Elections - Akey, Pat (Review of Financial Studies, 2015)
This paper investigates the value of firm political connections using a regression discontinuity design in a sample of close, off-cycle U.S. congressional elections. I compare firms donating to winning candidates and firms donating to losing candidates and find that postelection abnormal equity returns are 3% higher for firms donating to winning candidates. Connections to politicians serving on powerful congressional committees, such as appropriations and taxation, are especially valuable and impact contributing firms sales. Firms' campaign contributions are correlated with other political activities such as lobbying and hiring former government employees, suggesting that firms take coordinated actions to build political networks.